Combinatorial library of chalcogen-containing lipidoids for intracellular delivery of genome-editing proteins. (September 2018) - Li, Yamin; Yang, Tao; Yu, Yingjie; Shi, Nicola; Yang, Liu; Glass, Zachary; Bolinger, Justin; Finkel, Isaac James; Li, Wenhan; Xu, Qiaobing
Abstract: Protein based therapeutics with high specificities and low off-target effects are used for transient and accurate manipulation of cell functions. However, developing safe and efficient carriers for intracellular delivery of active therapeutic proteins is a long-standing challenge. Here we report a combinatorial library of chalcogen (O, S, Se) containing lipidoid nanoparticles (LNPs) as efficient nanocarriers for intracellular delivery of negatively supercharged Cre recombinase ((-30)GFP-Cre) and anionic Cas9:single-guide RNA (Cas9:sgRNA) ribonucleoprotein (RNP) for genome editing. The structure-activity relationship between the lipidoids and intracellular protein delivery efficiencies was explored and it was demonstrated that the newly developed LNPs are effective for gene recombination in vivo . Graphical abstract: Image 1